Rejection of per- and polyfluoroalkyl substances (PFASs) in aqueous film-forming foam by high-pressure membranes. (1st January 2021) - Liu, Charlie J.; Strathmann, Timothy J.; Bellona, Christopher
Highlights: >97% rejection of 42 different PFASs by nanofiltration and reverse osmosis. Membrane operating conditions marginally impacted PFAS rejection. Rejection reduced in groundwater matrix. Hydrophobic adsorption of PFASs to membranes, permeate spacer, and membrane system. Long-term membrane performance was not impacted by adsorption. Abstract: The ubiquitous use and manufacturing of per- and polyfluoroalkyl substances (PFASs) have led to the contamination of water resources worldwide. High-pressure membranes, including nanofiltration (NF) and reverse osmosis (RO), are increasingly being deployed for water treatment and may be an effective barrier to PFASs. However, the impact of membrane operating conditions, background water matrix, and solute adsorption on rejection of diverse PFASs by NF and RO remains unclear. Rejection of perfluoroalkyl acids (PFAAs) present in aqueous film-forming foam (AFFF) diluted into a laboratory electrolyte matrix by NF and RO spiral wound elements was >98% and >99%, respectively. Rejection of the same PFAAs present in an AFFF-impacted groundwater matrix by NF was lower, between 92-98%, and was attributed to background water matrix constituents. Operating conditions did not have a significant impact on rejection of PFASs with the exception of shorter chain perfluoroalkyl sulfonic acids (PFSAs) in the AFFF-impacted groundwater matrix, where rejection increased with increasing flux. Structure-activity analysis of 42 PFASs, including 10 PFAAs and 32 PFASs identified in AFFF through high-resolution mass spectrometry suspect screening methods, showed some correlation between rejection and compound molecular weight. Adsorptive losses of PFAAs, most notably longer-chain hydrophobic PFAAs, to the spiral wound membrane elements and the membrane system were observed. Adsorption of PFAAs to the permeate spacer was especially pronounced and may have implications of artificially high rejection values. Still, rejection of PFASs by NF remained consistently >98% over 13 days of continuous operation. Graphical abstract: Image, graphical abstract